Imobilização da enzima álcool desidrogenase em suportes alginato-quitosana e glioxil-agarose - Tacin, Mariana Vendrasco [UNESP] (2015)
Enzymes are important catalysts of biological reactions, and the microbiological origin has received special attention due to the ease of obtaining or even in the synthesis of genetically modified enzymes. The use of these biological catalysts in the industry is increasing with the advancement of studies and research of its properties and improving processes in which they are employed. The alcohol dehydrogenase (ADH) is an enzyme of industrial use and biotechnological important for quantitation of ethanol in biofuels and beverages, which in comparison with other methods, have shown to be most effective. The improvement of the enzyme stability is made by the immobilization process. Some methods of immobilization are most commonly applied because of the ease of preparation and/or immobilization of the enzyme on the support, for example, alginate-chitosan support. The supports alginate-chitosan and glyoxyl-agarose were used in this study to try to improve the stability of ADH. The aim of this study was to find a more effective method to immobilize the ADH and evaluate its stability against pH, temperature, variation of substrate concentration, addition of metal salts in the assay, among others. The results showed that there was interference of pH on the stability of alginate-chitosan beads precluding their use in this assay and when immobilized on glyoxyl agarose support was more stable at higher temperatures and pH, but showed good stability when stored.